The Journal of Peter Gordon, 1732-1735 - Sweet, Julie Anne (Wormsloe Foundation Publication, 1963)
The Journal of Peter Gordon, 1732-1735, provides a rare first-hand account of one of the original Georgia colonists. In his journal, Gordon, who served as chief bailiff of Savannah, Georgia, documents the challenges faced by the original settlers, criticism of the Trustees' policies for the colony, and interactions with indigenous peoples. His journal provides unique insight into the establishment of one of America's oldest colonies. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.